Hadronic contributions to the muon g − 2 in holographic QCD - Leutgeb Josef; Mager Jonas; Rebhan Anton (EPJ Web of Conferences, 2023)
We discuss the recent progress made in using bottom-up holographic QCD models in calculating hadronic contributions to the anomalous magnetic moment of the muon, in particular the hadronic light-by-light scattering contribution, where holographic QCD naturally satisfies the Melnikov-Vainshtein constraint by an infinite series of axial vector meson contributions.